Kikuchi-fujimoto disease - Parveen, Rezina; Rahman, SH; Yasmin, R; Quadir, MS; Muazzam, N; Alam, MN (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):95-98. The abstract of this article is available on the PubMed website